2015
DOI: 10.1016/j.midw.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh no, no, no, we haven׳t got time to be doing that’: Challenges encountered introducing a breast-feeding support intervention on a postnatal ward

Abstract: Citation: Hunter, L., Magill-Cuerden, J. and McCourt, C. (2015). 'Oh no, no, no, we haven't got time to be doing that': Challenges encountered introducing a breast-feeding support intervention on a postnatal ward. Midwifery, 31(8), pp. 798-804. doi: 10.1016Midwifery, 31(8), pp. 798-804. doi: 10. /j.midw.2015 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent Implications for practice:Midwives and maternity support workers need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Research has shown that health professionals often focus their attention, support and guidance on first-time mothers, although the reasons reported for supplementation in our study apply to all groups, regardless of parity. 19,20 Our study focused on exposure to CM proteins within the first 24 hours of life to assess the impact of this brief exposure to cow's milk protein in infants who go on to breastfeed on development of subsequent CMPA. It remains to be determined if continued supplementation of formula in breastfeeding infants would promote or prevent sensitization through development of tolerance to the preferred antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that health professionals often focus their attention, support and guidance on first-time mothers, although the reasons reported for supplementation in our study apply to all groups, regardless of parity. 19,20 Our study focused on exposure to CM proteins within the first 24 hours of life to assess the impact of this brief exposure to cow's milk protein in infants who go on to breastfeed on development of subsequent CMPA. It remains to be determined if continued supplementation of formula in breastfeeding infants would promote or prevent sensitization through development of tolerance to the preferred antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Overstretched maternity services are a trend shared with other countries, and have resulted in time-pressed, frustrated and exhausted midwives-potentially leading to a rushed, brusque or chaotic approach to care (Lindberg et al, 2005;Dykes, 2006;McLachlan et al, 2008;McKellar et al, 2009;Deery and Hunter, 2010). Recent observational research found that time pressures on a UK postnatal ward were exacerbated by midwives having little control over their time, the organisation of their space or access to the women in their care (Hunter, 2014;Hunter et al, 2015). This was evidenced in frequent interruptions to midwives' work by colleagues wanting information or assistance, and a large number of professional and lay visitors to inpatients, which sometimes prevented midwives accessing women to provide care (Hunter et al, 2015).…”
Section: Workplace Stressmentioning
confidence: 99%
“…It has been noted that midwives and other health professionals can be particularly resistant to change, perhaps owing to the constant changes imposed in busy and stressful healthcare settings (Hunter & Warren, ). A perceived lack of control over their working environment is also known to predispose people to being particularly resistant to change (Hunter et al., ). The apparent ability of mindfulness to give participants a sense of control at work is therefore significant and suggests that the practice may help midwives make more positive adjustments to other workplace changes.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty and anxiety were apparent as the participants were challenged to "unfreeze" the existing status quo, including letting go of current coping mechanisms, before learning new ways of coping and endeavouring to incorporate these into their day-to-day lives (Cummings, Bridgman, & Brown, 2016 (Hunter & Warren, 2014). A perceived lack of control over their working environment is also known to predispose people to being particularly resistant to change (Hunter et al, 2015). The apparent ability of mindfulness to give participants a sense of control at work is therefore significant and suggests that the practice may help midwives make more positive adjustments to other workplace changes.…”
Section: Discussionmentioning
confidence: 99%